Correlation between the non-use of cooking oil fume extractors and bone mineral density in population aged 45 years and older in China: a cross-sectional study - Zhang, Haitao; Shi, Binhao; Yuan, Chunchun; Huang, Chen; Huang, Tingrui; Liao, Zhangyu; Zhu, Wenhao; Zhong, Wei; Xu, Hongbin; Ji, Jiangxun; Cai, Feihong; Chen, Yue; et al. (Frontiers in Endocrinology, 2024)
Introduction The correlation between the non-use of cooking oil fumes (COFs) extractors and bone mineral density (BMD) have not been clarified. Consequently, this study attempted to explore the impact of non-use COFs extractors on BMD in population aged 45 years and older based on a cross-sectional study. Methods This study was a cross-sectional study within the framework of an ongoing prospective population-based cohort study in China. The multivariate linear regression models were used to evaluate the correlation between the non-use of fume extractors in family cooking and total lumbar spine (LS), femoral neck (FN), total hip BMD and levels of bone metabolism markers. Results A total of 3433 participants were included in the final analyses, of which 2607 (75.93%) participants used fume extractors. The results of models indicated that there were significant correlations of the non-use of fume extractors on total LS BMD (β = -0.024, 95% CI, -0.036, -0.012, p < 0.001), PINP (β = 4.363, 95% CI, 2.371, 6.356, p < 0.001) and ALP (β = 4.555, 95% CI, 2.593, 6.517, p < 0.001) levels. Conclusions This study verified that the use of fume extractors is an efficacious measure to prevent LS bone loss. For the sake of public bone health, people should install a fume extractor in the kitchen and use it routinely when cooking.